ปัจจัยที่ส่งผลต่อความสุขในการปฏิบัติงานของบุคลากรสายสนับสนุนในสถาบันอุดมศึกษาของมหาวิทยาลัยราชภัฏสงขลา - พิชยดนย์ ชายมะ (มหาวิทยาลัยสงขลานครินทร์, 2023)
This research, Factors Affecting Happiness at Work of the Supporting Staff in Higher Educational Institutions of Songkhla Rajabhat University, aimed at (1) studying the level of happiness at work of the supporting staff in higher educational institutions of Songkhla Rajabhat University, (2) comparing happiness at work classified by the personal factors of supporting staff in higher educational institutions of Songkhla Rajabhat University, and (3) studying the operational factors affecting happiness at work of supporting staff in higher educational institutions of Songkhla Rajabhat University. The sampling participants on this quantitative research were 163 of supporting staff in higher educational institutions of Songkhla Rajabhat University. Moreover, this research used stratified random sampling. The research tool was a questionnaire to measure performance factors, happiness at work, and 8 happiness factors (HAPPY 8). The statistics used for data analysis were frequency distribution, percentage, mean, standard deviation, correlation coefficient and multiple regression analysis. The study found that the level of happiness at work of supporting staff in higher educational institutions of Songkhla Rajabhat University and the overall 8 happiness factors were in the happy level (Happy). The happiness level of gaining knowledge was higher than other aspects, followed by good family. However, the lowest level of happiness was the factor of relaxation. There was a statistical significance at the 0.01 level for the operational factors affecting the happiness at work of supporting staff in higher educational institutions of Songkhla Rajabhat University. Considering individually, it was found that the item with a higher level of opinion than the others was the relationship factor, and the item with the lowest level of opinion was the factor of acceptance.